Literacy Education and Social Capital: A Study of Women’s Involvement in Community Development Projects in Southwestern Nigeria - Babalola, Adejoke Clara; Fasokun, Thomas Olusola (Journal of Education and Research, 2019)
The study examines the relationship between social capital and women’s involvement in a community development project; assesses the relationship between rural women literacy level and social capital leverage, and determines the interaction effect of literacy level and social capital leverage on rural women involved in community development projects. This research was conducted in Southwestern Nigeria using a descriptive survey research design followed by qualitative methods for in-depth analysis. A multi-stage sampling procedure was used to select 720 rural women from randomly selected three states in Southwestern Nigeria. Moreover, we also conducted in-depth interviews with 12 women (6 each of literate and non-literate) who had indicated participation in community development projects and conducted a focus group discussion in each of the three selected states. The findings reveal that the most significant predictors of rural women involvement in community development are: participation in adult literacy programme; literacy level; strong interaction with people; membership of community development committees; participation in the decision making process and discussion of development issues with friends. Moreover, the number of literate women who made use of social capital to participate in community development is high. The study, therefore, concludes that the relationship between literacy and social capital is strong.